If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -3)(2x + 9) = 9(3x + 2) Reorder the terms: (-3 + X)(2x + 9) = 9(3x + 2) Reorder the terms: (-3 + X)(9 + 2x) = 9(3x + 2) Multiply (-3 + X) * (9 + 2x) (-3(9 + 2x) + X(9 + 2x)) = 9(3x + 2) ((9 * -3 + 2x * -3) + X(9 + 2x)) = 9(3x + 2) ((-27 + -6x) + X(9 + 2x)) = 9(3x + 2) (-27 + -6x + (9 * X + 2x * X)) = 9(3x + 2) (-27 + -6x + (9X + 2xX)) = 9(3x + 2) Reorder the terms: (-27 + 9X + -6x + 2xX) = 9(3x + 2) (-27 + 9X + -6x + 2xX) = 9(3x + 2) Reorder the terms: -27 + 9X + -6x + 2xX = 9(2 + 3x) -27 + 9X + -6x + 2xX = (2 * 9 + 3x * 9) -27 + 9X + -6x + 2xX = (18 + 27x) Solving -27 + 9X + -6x + 2xX = 18 + 27x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 9X + -6x + 27 + 2xX = 18 + 27 + 27x Reorder the terms: -27 + 27 + 9X + -6x + 2xX = 18 + 27 + 27x Combine like terms: -27 + 27 = 0 0 + 9X + -6x + 2xX = 18 + 27 + 27x 9X + -6x + 2xX = 18 + 27 + 27x Combine like terms: 18 + 27 = 45 9X + -6x + 2xX = 45 + 27x Add '6x' to each side of the equation. 9X + -6x + 6x + 2xX = 45 + 27x + 6x Combine like terms: -6x + 6x = 0 9X + 0 + 2xX = 45 + 27x + 6x 9X + 2xX = 45 + 27x + 6x Combine like terms: 27x + 6x = 33x 9X + 2xX = 45 + 33x Reorder the terms: -45 + 9X + -33x + 2xX = 45 + 33x + -45 + -33x Reorder the terms: -45 + 9X + -33x + 2xX = 45 + -45 + 33x + -33x Combine like terms: 45 + -45 = 0 -45 + 9X + -33x + 2xX = 0 + 33x + -33x -45 + 9X + -33x + 2xX = 33x + -33x Combine like terms: 33x + -33x = 0 -45 + 9X + -33x + 2xX = 0 The solution to this equation could not be determined.
| y-10=9y-6 | | ml=7.3l | | 9w=2*9w | | 4cosx-2=cosx | | 2^-1=1/64 | | 9x^2-9x-15=0 | | 6+2x+3y=48 | | 7b+2a-(3a+2b)= | | 4x-6=2(x+1) | | (X-786)(x+4)=0 | | (X-393)(x+4)=0 | | 2x+5(2.5)=20 | | 27=(27-15x)*2 | | 5779/19= | | -100=0.1x(30+-1x) | | -100=0.1(30-x) | | arccos(3/5) | | 4--7= | | 65+70=78 | | 12/x=6/11 | | x/2=3/10 | | 12/x=6/9 | | -55+b+39.68=-71.03 | | -55+b+39.68=71.03 | | 10z+1=3z+6 | | 5x-80x^2=0 | | 3x^3-9=0 | | 1=8tan(2x+1)-3 | | 4/25-x^2/81 | | 4(m+1)= | | 9x^2-9x+4=7x^2 | | 2x^3+6x^2+6x+6=0 |